JOB PLACEMENT, TRANSFORMATIONAL LEADERSHIP, AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION OF MILLENNIAL EMPLOYEES AT THE UNIVERSITY OF GRIYA PERSADA MEDIATED THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE - Naseha Elkrima; Bambang Satriawan; Nurhatisyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The shift in human resource management (HRM) paradigms and organizational strategies has become increasingly important in the era of globalization, especially with the growing dominance of the millennial generation in the workforce. One of the main challenges faced by organizations today is the gap between the expectations and realities experienced by millennial employees in the workplace, particularly regarding fairness, communication, and opportunities for personal development. This study aims to examine the influence of job placement, transformational leadership, and organizational culture on job satisfaction among millennial employees at Universitas Griya Persada, with work motivation serving as a mediating variable. This research adopts a quantitative approach by distributing online questionnaires to non-academic millennial employees. The data were analyzed using Structural Equation Modeling (SEM). The results show that transformational leadership and organizational culture have a positive and significant direct influence on job satisfaction. Meanwhile, job placement does not have a significant direct effect but shows a significant indirect influence through work motivation. Furthermore, work motivation itself was found to have a positive and significant impact on job satisfaction and mediates the relationship between the independent variables and job satisfaction. These findings highlight the importance of applying an inspirational leadership style, fostering an inclusive organizational culture, and ensuring proper job placement that aligns with employees’ competencies and aspirations to enhance job satisfaction among millennials. This study offers practical insights for developing HRM strategies that are aligned with the values and characteristics of the millennial generation, particularly within the context of higher education institutions.